3D.001 Post-crash trauma care: first-responder training for the traffic police in Makwanpur, Nepal. (14th March 2021) - Smart, Gary; Banstola, Amrit; Raut, Raju; Ghimire, Krishna; Joshi, Elisha; Joshi, Sunil Kumar; Mytton, Julie
Abstract : Context: Road crashes are the 7th leading cause of mortality in Nepal, but there are poorly developed nationwide emergency medical services. Contributing to achieving SDG 3.6 to reduce deaths from road crashes, we designed and evaluated the feasibility of a bespoke first-responder training programme for traffic police in Nepal. Process: Interviews with traffic police informed course design. 29 officers in Makwanpur District completed before and after knowledge and confidence assessments prior to a 3-day first-response course. Police teams were supplied with first response packs and asked to complete report forms when first-responder skills were used. Follow-up assessments and interviews at 6-months explored retention and experiences of applying first-response skills. Analysis: Pre-course assessments showed that although 97% of participants believed giving first-aid was their responsibility, knowledge and confidence levels were low and minimal training was reported. 95% had experience of transporting road crash victims to hospital. Post-test knowledge scores improved by 40% to 75%. Confidence levels improved post-course and remained high at 6-months. Outcomes: During 6-months follow up, 27 participants attended 303 crashes where people were injured. 44% of participants used at least one first-response skill from the course; applying skills on 92 occasions, however only 3 report-forms were completed. Barriers to providing at-scene treatment included; patients already transported to hospital prior to police arrival; resistance from relatives/bystanders and competing police duties. Learning Outcomes: Delivering the first-response programme for the traffic-police is feasible and knowledge and confidence can be retained. Barriers to using and reporting first-response skills need to be addressed.